2016
DOI: 10.1186/s41155-016-0007-y
|View full text |Cite
|
Sign up to set email alerts
|

Causal attribution among women with breast cancer

Abstract: Causal attribution among women with breast cancer was studied. The study included 157 women outpatients with breast cancer. A form for sociodemographic and clinical data and the Revised Illness Perception Questionnaire (IPQ-R) were used. The results showed that women attributed breast cancer primarily to psychological causes, which does not correspond to known multifactorial causes validated by the scientific community. Providing high quality, patient-centered care requires sensitivity to breast cancer women's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 13 publications
(19 reference statements)
0
16
0
1
Order By: Relevance
“…Spearman's nonparametric correlation test was employed to analyze the strength and direction of the relationship between illness perception, risk perception and sociodemographic variables. The open answers to the causes of the illness were classified according to the content, based on the criteria used in the literature (Peuker, Armiliato, Souza, & Castro, 2016). Two independent judges and experts in the subject assessed and categorized all the answers, and, in case of disagreement, a third judge set the appropriate category.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spearman's nonparametric correlation test was employed to analyze the strength and direction of the relationship between illness perception, risk perception and sociodemographic variables. The open answers to the causes of the illness were classified according to the content, based on the criteria used in the literature (Peuker, Armiliato, Souza, & Castro, 2016). Two independent judges and experts in the subject assessed and categorized all the answers, and, in case of disagreement, a third judge set the appropriate category.…”
Section: Discussionmentioning
confidence: 99%
“…Literature has shown that women who fall ill with breast cancer tend to blame and assign the etiology of the illness to emotional issues (e.g. family problems, sorrows, worries) (Kaptein et al, 2015;Peuker et al, 2016;Thomson et al, 2014). From an important event such as having cancer, perceptions about the illness, particularly causal attributions may be changed spontaneously so that the person can make sense of their illness (Peuker et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common attributions in women with breast cancer in Western Australia were to mental or emotional factors (46.3%), especially stress, followed by lifestyle factors (38.6%) and physiological factors (37.5%), particularly relating to hormonal history (20). Brazilian woman with BC attributed breast cancer primarily to psychological causes (21). It was also found that the Dutch patients with BC think that the psychological factors mostly cause the disease (1).…”
mentioning
confidence: 99%
“…Assim, apenas informação não é suficiente para mudar comportamento em saúde (Castro et al, 2015;Peuker, Armiliato, Souza & Castro, 2016), sendo necessário criar estratégias de educação em saúde baseado não só nas informações concretas da doença, mas nas crenças das pessoas a respeito delas (Lima, Peuker & Castro, 2016;Castro et al, 2015). Os materiais elaborados e destinados a ações de promoção em saúde devem abranger sempre estratégias de educação, incluindo conteúdos que propi-ciam a adesão dos pacientes a determinado tratamento e/ ou à prevenção de comportamento que levem aos fatores de risco de uma determinada doença (Gorayeb & Nakao, 2015).…”
unclassified